DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR THE SIMULTANEOUS ESTIMATION OF LEDIPASVIR AND SOFOSBUVIR IN BULK AND PHARMACEUTICAL DOSAGE FORM (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The day by day new combinations drugs are being introduced in market. Then the multiple therapeutic agents which acts at different sites are used in the management of various diseases and disorders are done. Thus it is necessary to develop methods for analysis with the help of number of analytical techniques which are available for the estimation of the drugs in combination. The analyst were determine the Specific, accurate, simple, selective and stability-indicating RP-HPLC method is developed and validated for simultaneous determination of sofosbuvir and ledipasvir in tablet dosage form. RP-HPLC method was performed on the systronics isocratic HPLC System equipped with SP930 D HPLC pump and dual wavelength UV-VIS detector and C18 column (250 mm × 4.6 mm, 5μm), using the mobile phase (Methanol: Water 83:17 v/v) pH 3.0 with 0.05% acidic acid at a flow rate of 1.0 ml/min, injection volume 20μl and UV detection at 245 nm. This method is validated according to BP, USP and ICH requirements for new methods, which include accuracy, precision, robustness, ruggedness, lod, loq, linearity and range. Linear relationships were obtained in the ranges of 10-50μg/ml and 40-200μg/ml with correlation coefficients of 0.9991 and 0.9994 at Rt value of 7.45 min and 3.50 min for sofosbuvir and ledipasvir respectively. The forced degradation studies as acidity, alkalinity, oxidation and hydrolytic degradation were performed according to ICH guidelines.